Pengaruh Fitur Layanan Mesin EDC, Transaction Fee, dan Kualitas Jaringan terhadap Kepuasan Nasabah - Sri Pebrianti, I Gusti Ayu; Hartati, Putu Sri (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
One of the important things that every company needs to do and pay attention to is customer satisfaction. Considering the importance of customer satisfaction, it is very necessary to pay attention to the factors that influence it, including EDC machine service features, transaction fees and network quality. Likewise, the BRI Link 2D Mesari Agent, Blahkiuh Village, Abiansemal, in an effort to increase customer satisfaction in transactions, always pays attention to the EDC machine service features, transaction fees and network quality. “The method of collecting data in this research was carried out by means of observation, interviews, documentation, literature study and questionnaires. Questionnaires were given to 99 respondents, and then analyzed using multiple linear regression, determination, t test and F test. The results of this research are that the influence of EDC machine service features on customer satisfaction is positive and significant. The effect of transaction fees on customer satisfaction is positive and significant. The effect of network quality on customer satisfaction is positive and significant.” The influence of EDC machine service features, transaction fees and network quality on customer satisfaction at the BRI Link 2D Mesari Agent, Blahkiuh Village, Abiansemal is positive and significant.